Interventional Radiology in the Diagnosis and Management of Acute Gastrointestinal Bleeding - Faisal Abdullah S Alqhtani, Omair Saad M Alqahtani, Abdulrahman Saad N Alasiri, Saad Saeed O Alshahrani, Sarah Abdulaziz A Alshadidi; Razan Saeed A Talhan, Alyaa Ahmad M Alqarni, Aoodhah Mohammed S Arim, Abdullah Mohammed Ali Alshehri, Ibtihaj Mohammed Alqahtani (Journal of International Crisis and Risk Communication Research, 2024)
Acute gastrointestinal bleeding (GIB) is a critical medical emergency that poses significant risks to patient morbidity and mortality. It can arise from various etiologies, including peptic ulcers, diverticular disease, malignancies, and vascular anomalies. The management of acute GIB has evolved considerably, with interventional radiology (IR) emerging as a vital component in both diagnosis and treatment. This review explores the role of interventional radiology in the management of acute GIB, emphasizing its diagnostic capabilities and therapeutic interventions. Diagnostic angiography is a cornerstone of IR, allowing for the real-time visualization of the vascular supply to the gastrointestinal tract. This technique is particularly beneficial in cases where the source of bleeding is not readily apparent through conventional imaging methods. The ability to identify active bleeding enables targeted therapeutic interventions, such as embolization. Therapeutic embolization involves the selective occlusion of bleeding vessels using various embolic agents, including coils, particles, and liquid agents. This minimally invasive approach has demonstrated high success rates in controlling hemorrhage, with reported efficacy ranging from 70% to 90%. In addition to embolization, stenting is another important IR technique, particularly in cases involving malignant obstruction or strictures. Endovascular stents can restore patency in obstructed vessels, improving blood flow and reducing the risk of further bleeding. The use of stenting has been associated with enhanced patient outcomes, including decreased need for surgical intervention and shorter hospital stays. Despite the advantages of interventional radiology, potential complications such as vessel injury and non-target embolization must be considered. A multidisciplinary approach involving gastroenterologists, surgeons, and interventional radiologists is essential for optimizing patient care. As the field of interventional radiology continues to advance, ongoing research and technological innovations promise to further enhance the management of acute gastrointestinal bleeding, ultimately improving patient safety and outcomes. This review underscores the critical role of interventional radiology in the comprehensive management of acute GIB, highlighting its potential to transform patient care in this challenging clinical scenario.